Ginsenoside Rg3 treats acute radiation proctitis through the TLR4/MyD88/NF-κB pathway and regulation of intestinal flora - Duan, Xiaoyu; Cai, Hongyi; Hu, Tingting; Lin, Lili; Zeng, Lu; Wang, Huixia; Cao, Lei; Li, Xuxia (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives This study aimed to investigate the protective effect of ginsenoside Rg3 (GRg3) against acute radiation proctitis (ARP) in rats. Methods Wistar rats were randomly divided into control, model, dexamethasone-positive, GRg3 low-dose, GRg3 medium-dose, and GRg3 high-dose groups. The ARP rat model was established by a single 22-Gy irradiation of 6 MV) X-rays. The distribution and function of intestinal flora were detected using 16S rRNA high-throughput sequencing, rectal tissue was observed by hematoxylin and eosin (H&E) staining, the expression of interleukin 1β (IL-1β) and IL-10 inflammatory factors was detected by ELISA, and mRNA and protein expression of toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) were detected by RT-qPCR and Western blotting, respectively. Results GRg3 improved the symptoms of ARP in rats in a dose-dependent manner. The species distribution of intestinal flora in GRg3 rats was significantly different from that in ARP rats. These differences were more significant in the high-dose group, where the numbers of Ruminococcus, Lactobacillus, and other beneficial bacteria were significantly increased, whereas those of Escherichia, Alloprevotella, and other harmful bacteria were decreased. In addition, GRg3 was closely related to amino acid metabolism. After GRg3 treatment, the mRNA and protein expression of TLR4, MyD88, and NF-κB in rectal tissue was significantly down-regulated, and the level of downstream inflammatory factor IL-1β decreased, whereas that of IL-10 increased. Conclusion Our study indicated GRg3 as a new compound for the treatment of ARP by inhibiting the TLR4/MyD88/NF-κB pathway, down-regulating the expression of proinflammatory factors, thus effectively regulating intestinal flora and reducing inflammatory reactions.